Italy : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights Italy's assesses measures undertaken to revive economic growth. Italy is vulnerable to a renewal of euro area tension and risks from domestic policy slippages, stalling of structural reforms, and banking distress that could undermine confidence. The government has taken steps to liberalize services, open the energy sector, and improve the labor market, but more is needed to boost productivity and raise Italy's low employment rate. The IMF report shows that banks have improved their capital positions, but continue to suffer from weak asset quality and profitability.